Metallographic Analysis of Nakajima Tests for the Evaluation of the Failure Developments - Affronti, Emanuela; Merklein, Marion (Procedia Engineering, 2017)
The material characterisation in sheet metal forming is significantly improved with the introduction of optical measurement systems. The optical measurement is based on the digital image correlation (DIC) technique, which provides accurate strain measurement of the local strain distribution on specimens. The changes of the stochastic distribution due to the forming are therefore used in order to measure displacements and deformations. An acknowledged application of the DIC technique is the evaluation of the forming limit curve (FLC) for sheet metals. Typically, the FLC is evaluated by conducting Nakajima tests. The Nakajima test is a stretch forming-based test and allows the analysis of stretching at different stress conditions. A previous investigation based on pattern recognition on Nakajima tests has shown that for a conventional deep drawing steel DC04 the pattern evolution on the strain distribution during the test can be examined in order to predict the material failure. However, even if the investigation shows promising results, the correspondence between pattern on the surface and changes in the material structure is missing. The aim of the present work is an analysis of the surface structure of Nakajima tests at different stress states and drawing depths. The correlation between surface modifications and failure behaviour is conducted on the deep drawing steel DC04. The scanning electron microscope (SEM) (Merlin Zeiss GmbH) is employed in order to investigate the evolution of the surface at different strain conditions. The results of the surface and the metallographic investigation are finally compared with the forming limit prediction of the FLC and the failure behaviour at different stress conditions is discussed.
LFT Import::2019-08-05 (2227)
Keywords: forming limit; metal forming; metallography